Cover Feature: Rational Development of Guanidinate and Amidinate Based Cerium and Ytterbium Complexes as Atomic Layer Deposition Precursors: Synthesis, Modeling, and Application (Chem. Eur. J. 15/2021). Issue 15 (7th January 2021) - Kaur, Parmish; Mai, Lukas; Muriqi, Arbresha; Zanders, David; Ghiyasi, Ramin; Safdar, Muhammad; Boysen, Nils; Winter, Manuela; Nolan, Michael; Karppinen, Maarit; Devi, Anjana
Abstract : New metalorganic precursors of cerium and ytterbium have been developed in this systematic study. Among them, a homoleptic guanidinate‐based cerium complex has been demonstrated as a promising precursor for water‐assisted atomic layer deposition of CeO2 thin films. More information can be found in the Full Paper by A. Devi et al. on page 4913 .